Hydrogen evolution reaction performance of the molybdenum disulfide/nickel–phosphorus composites in alkaline solution. (9th November 2016) - Song, Laizhou; Wang, Xiuli; Wen, Fusheng; Niu, Lijing; Shi, Xuanming; Yan, Jiayun
Abstract: The low phosphorus (LP), medium phosphorus (MP), and high phosphorus (HP) three nickel–phosphorus (NiP) powders were employed as supports of molybdenum disulfide (MoS2 ) to fabricate MoS2 /NiP composites (MoS2 /Ni–LP, MoS2 /Ni–MP, and MoS2 /Ni–HP) via a hydrothermal technique. Crystal structures, morphologies, components and hydrogen evolution reaction (HER) performances of them were characterized and evaluated. During the incorporation between MoS2 and NiP, the crystallization of NiP powders and the presence of metastable nickel phosphides can be validated; also, the 2H-MoS2 tends to transfer to the phase of 1T-MoS2 . Compared with MoS2 and NiP samples, MoS2 /NiP composites show a higher HER property. Prominent HER behaviors of the composites can be due to the presence of monolayer 1T-MoS2 on the surface, the excellent conductivity of NiP powder at the bottom, as well as the coexistence of nickel phosphides. Among the three composites, MoS2 /Ni–MP exhibits the remarkably electrocatalytic activity. Highlights: MoS2 /NiP composites exhibit a higher HER property than other samples. Among three composite samples, HER activity of MoS2 /Ni–MP is the best. Crystallization of NiP and presence of nickel phosphides can be validated. MoS2 tends to transfer from 2H-MoS2 to 1T-MoS2 . MoS2 /Ni–MP sample deserves to be recommended as a HER catalyst.